2012
DOI: 10.1111/j.1756-185x.2012.01709.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic ultrasound versus sham ultrasound for the management of patients with knee osteoarthritis: a randomized double‐blind controlled clinical study

Abstract: US therapy is safe but use of US in addition to conventional physical therapy programs seems to have no further significant effect in people with knee OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 29 publications
2
45
0
3
Order By: Relevance
“…However, there are divergences about its efficacy (36). Ulus et al (37) found no significant differences between the use of US and placebo in the VAS scores for patients with knee osteoarthritis. In our study, US reduced pain after therapy; however, effect presented larger size when compared with the use associated with Copaíba oil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are divergences about its efficacy (36). Ulus et al (37) found no significant differences between the use of US and placebo in the VAS scores for patients with knee osteoarthritis. In our study, US reduced pain after therapy; however, effect presented larger size when compared with the use associated with Copaíba oil.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study (11), US reduced pain and, therefore, increased the mobility of patients with mild knee osteoarthritis. On the other hand, Ulus et al (12) observed that US did not bring more significant improvements to a control group for the variables of pain, physical function, disability and psychological state of patients with knee osteoarthritis. The latest Cochrane database review (13) Patients were randomly divided into three groups: ultrasound group (US); ultrasound group associated with Copaíba oil (US+CO) and a Copaíba oil group (CO).…”
Section: Introductionmentioning
confidence: 99%
“…Así, la búsqueda bibliográfica concluyó con 13 ECC [11][12][13][14][15][16][17][18][19][20][21][22][23] (figura 1). La tabla 1 muestra los artículos incluidos en la revisión describiendo el objetivo, la población del estudio, las variables, el análisis y los principales resultados.…”
Section: Bibliográficaunclassified
“…Esto pudo estar influenciado por la falta de poder de este estudio debido a las pérdidas y exclusiones luego de la aleatorización. Ulus et al 18 realizaron 15 sesiones de intervención en un grupo de UST continuo y otro placebo sin encontrar diferencias significativas entre los grupos.…”
Section: Bibliográficaunclassified
See 1 more Smart Citation